2010
DOI: 10.1200/jco.2009.26.9589
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP)-Ribose Polymerase Inhibition: Frequent Durable Responses in BRCA Carrier Ovarian Cancer Correlating With Platinum-Free Interval

Abstract: Olaparib has antitumor activity in BRCA1/2 mutation ovarian cancer, which is associated with platinum sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
609
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(648 citation statements)
references
References 26 publications
33
609
1
5
Order By: Relevance
“…This subgroup may be amenable to specific therapeutic strategies such as inhibitors of the PARP enzyme. 32,[81][82][83]130,131 Consistent with this hypothesis, results of PARP inhibitor phase I and phase II clinical trials that have included patients with BRCA-deficient tumors have been encouraging [132][133][134] and sustained responses in patients with BRCA1/2-deficient breast or ovarian metastatic cancers have been observed. Furthermore, preliminary results of a phase II clinical trial revealed that addition of BSI-201, a PARP inhibitor, to gemcitabine/carboplatin chemotherapy led to a significantly increased clinical benefit and longer progression-free survival.…”
Section: Clinical Behavior Of Basal-like and Triple-negative Breast Cmentioning
confidence: 76%
“…This subgroup may be amenable to specific therapeutic strategies such as inhibitors of the PARP enzyme. 32,[81][82][83]130,131 Consistent with this hypothesis, results of PARP inhibitor phase I and phase II clinical trials that have included patients with BRCA-deficient tumors have been encouraging [132][133][134] and sustained responses in patients with BRCA1/2-deficient breast or ovarian metastatic cancers have been observed. Furthermore, preliminary results of a phase II clinical trial revealed that addition of BSI-201, a PARP inhibitor, to gemcitabine/carboplatin chemotherapy led to a significantly increased clinical benefit and longer progression-free survival.…”
Section: Clinical Behavior Of Basal-like and Triple-negative Breast Cmentioning
confidence: 76%
“…In the absence of HR, as occurs when BRCA mutations are present, these DSBs are repaired by error-prone forms of DSB, such as non-homologous en-joining potentially resulting in accumulation of gene aberrations and loss of cell viability. 106,107 Significant efficacy has been established for PARP inhibitors in BRCA-mutated breast and ovarian tumours, [108][109][110] although the evidence for PCa is still limited. Clinical trials are currently ongoing to assess the role of PARP inhibitors in PCa BRCA-related, as well as in sporadic tumours.…”
Section: Discussionmentioning
confidence: 99%
“…101,[108][109][110] The aggressive phenotype and poor prognosis associated with PCa in patients with germline BRCA mutations is very likely to be associated with a different cancer biology from BRCA wild-type PCa. The identification of these differential molecular characteristics could be essential in tailoring treatment for this population, but it may also be of great importance for the management of some sporadic PCa cases which may have similar clinical characteristics and aggressive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed anti-tumour effects in human breast and ovarian cancers in patients carrying BRCA1 or BRCA2 germline mutations. [249][250][251][252][253][254] Of note, although ovarian cancer patients treated for high-grade epithelial cancers not harbouring BRCA1/2 germline mutations responded to PARP inhibition with Olaparib with a response rate similar to that of BRCA1/2 mutation carriers, no response to Olaparib monotherapy was recorded among patients treated for triple-negative breast cancer harbouring wild-type BRCA1/2. 253 BRCA1/2 somatic and germline mutations are observed more frequently in ovarian (420%) as compared with breast cancers; 255 yet, the finding of a high response rate to PARP inhibitors in high-grade ovarian cancers suggests alternative mechanisms of HRR inactivation may operate in addition.…”
Section: Homologous Recombination Repairmentioning
confidence: 99%